Analysis of Effective Power Diesel Engine Test RIG Mod.E TD301 Using Biodiesel Fuel from Coconut Oil - Baso Riadi Husda; Muhammad Agung; Aminuddin Aminuddin; Wahyul Imam (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
This study aims to determine the Effective Power of Diesel Engine Test Rig Mod.E TD301 Using Biodiesel Fuel From Coconut Oil. The research was carried out at the Energy Conversion Machine testing laboratory at the State University of Makakassar from November 2020 to December 2020. Tests for the properties and chemistry of Biodiesel were carried out at the Sucofindo Cibitung laboratory. In this study, researchers used 5 types of fuel oil, namely, 1. Pertamina diesel, 2. a mixture of 75% Pertamina diesel with 25% biodiesel, 3. a mixture of 50% Pertamina diesel with 50% biodiesel, 4. a mixture of 25% Pertamina diesel with 75 % biodiesel, 5. 100% biodiesel. Of the five fuels, the highest effective power is obtained from 100% biodiesel fuel and the lowest is Of the five fuels, the highest effective power is obtained from 100% biodiesel fuel and the lowest is obtained from Pertamina diesel fuel rotation. Penelitian ini bertujuan untuk mengetahui Daya Efektif Mesin Diesel Test Rig Mod.E TD301 Dengan Mengunakan Bahan Bakar Biodiesel Dari Minyak Kelapa. Penelitian di laksanakan pada laboratorium pengujian Mesin Konversi Energi Universitas Negeri Makakassar pada bulan November 2020 sampai bulan Desember 2020. Pengujian sifat dan kimia Biodiesel di laksanakan pada laboratorium Sucofindo Cibitung. Pada penelitian ini peneliti menggunakan 5 macam bahan bakar minyak yaitu, 1. Solar pertamina, 2. campuran 75% solar pertamina dengan biodiesel 25%, 3. campuran 50% solar pertamina dengan 50% biodiesel, 4. campuran 25% solar pertamina dengan 75% biodiesel, 5. 100% biodiesel. Dari kelima bahan bakar tersebut Daya Efektif yang paling besar di dapatkan pada bahan bakar biodiesel 100% dan terendah di dapat pada bahan bakar solar pertamina.